Facilitators and barriers in preventing doping among recreational athletes: A qualitative interview study among police officers - Kvillemo, Pia; Strandberg, Anna K.; Elgán, Tobias H.; Gripenberg, Johanna (Frontiers in Public Health, 2022)
Background: Doping is a societal problem associated with health problems, violence and other crimes, especially when combined with alcohol and drugs. Elite, as well as recreational athletes who exercise in gyms may use doping to enhance their performance and/or improve their appearance. According to Swedish law, manufacturing, selling, supplying, possessing, and using anabolic androgenic steroids and growth hormones is forbidden. Exceptions apply if these substances are used for medical purposes and prescribed by doctors. As doping is illegal, the police authority is vital in counteracting doping. Aim: We aimed to identify facilitators and barriers to effective doping prevention at gyms by examining police officers' views on doping as a societal problem, their experiences of doping prevention efforts, and their perceptions on what enables or hinders doping prevention. Methods: Interviews with police officers (n = 15) were conducted from December 2021 to May 2022. The interviews were recorded and transcribed verbatim. A targeted content analysis of the material was performed. Result: Facilitators for effective doping prevention involving the police included the recognition of doping as a societal problem; mobilization of key actors; motivated police management and officers; adequate resource allocation; collaboration between the police, gyms, and other relevant authorities; and skills development for police and other professions. Barriers to effective doping prevention included a lack of knowledge about doping, time-consuming processes around the detection and collection of evidence in doping offenses, and competing tasks for police officers. Conclusion: Doping prevention should become more efficient by taking advantage of existing facilitators and removing remaining barriers. This study could guide recommendations linked to the police organization and the surrounding society regarding doping prevention.